Interaction of contextual, setting and implementation factors on a podoconiosis intervention in Rural Ethiopia: Results from a qualitative study - Kibur Engdawork; Getnet Tadele; Gail Davey; Papreen Nahar; Shahaduz Zaman (PLoS ONE, 2025)
Social science perspectives enable more holistic approaches to the evaluation of health interventions. Balance between context, setting and implementation is key to the sustainable impact of health interventions. However, little is known about how the implementation of interventions against Neglected Tropical Diseases interacts with context and settings, or the influence of the interaction on intervention outcomes. We conducted a qualitative evaluation of a podoconiosis intervention in Northwestern Ethiopia, and collected data on intervention implementation, context, setting and relations among these elements between 10/04/2022 and 29/07/2022. Our system and network analyses revealed that the context, setting and implementation of the intervention interacted formally and informally across macro, meso and micro levels during intervention delivery and created constraints on the intervention. In future, implementers must design programs that can withstand the constraining effects of contextual and related factors to effectively deliver activities and institutionalize NTD services at the community level. These programs must be supported by simultaneous efforts to mobilize institutions and local actors to ensure reflection on priorities and local solutions. Integrating social science perspectives into intervention evaluation enables better analysis and understanding of the factors influencing health interventions.